2019
DOI: 10.1007/s10531-019-01824-6
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of citizen scientists on open access to UK butterfly and moth occurrence data

Abstract: Citizen science plays an increasingly important role in biodiversity research and conservation, enabling large volumes of data to be gathered across extensive spatial scales in a cost-effective manner. Open access increases the utility of such data, informing land-use decisions that may affect species persistence, enhancing transparency and encouraging proliferation of research applications. However, open access provision of recent, fine-scale spatial information on the locations of species may also prompt leg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…Few studies have examined volunteer perspectives on the handling of citizen science data. Fox et al (2019) found that volunteers in a large-scale UK project supported open access in principle but for its practice supported cautionary actions to protect sensitive information and restrict commercial reuse of data. Groom et al (2017) reviewed the open access nature of biodiversity observation data contributed to GBIF (one of largest biodiversity data repositories).…”
Section: Decision-makers and Data-producersmentioning
confidence: 99%
“…Few studies have examined volunteer perspectives on the handling of citizen science data. Fox et al (2019) found that volunteers in a large-scale UK project supported open access in principle but for its practice supported cautionary actions to protect sensitive information and restrict commercial reuse of data. Groom et al (2017) reviewed the open access nature of biodiversity observation data contributed to GBIF (one of largest biodiversity data repositories).…”
Section: Decision-makers and Data-producersmentioning
confidence: 99%
“…The publishing rate of original data collected with citizen science was somewhat higher than average, although still fewer than half of the articles based on original citizen science published their data. This is problematic, because studies have shown that citizen science participants generally expect and want their data to be made available for research, conservation, and policymaking (Chandler et al 2017 , Ganzevoort et al 2017 , Groom et al 2017 , Fox et al 2019 , Larson et al 2020 ). Further integration of citizen science with open biodiversity data aggregators should therefore be a priority.…”
Section: How Often Are Presence-only Data Made Available For Reuse?mentioning
confidence: 99%
“…Open Science (Nosek et al, 2015) is an ongoing initiative that seeks to make the results of scientific endeavours accessible to all; open data is one critical dimension that envisages data being made available without copyright or any other restrictions. While it is often assumed that data produced by the CitSci community are freely available, this is often not the case as the community can face hurdles in making their data open and freely available (Fox et al, 2019;Pearce-Higgins et al, 2018). A study by Groom et al (2017) of datasets in the Global Biodiversity Information Facility (GBIF) (https://www.gbif.org/) indicated that datasets from the volunteer community are amongst the most restrictive in the way they could be used.…”
Section: Lack Of Support For Open Sciencementioning
confidence: 99%